Education and development; females' education and fertility reduction in Africa: The case of Tigray, Ethiopia. Issue 2 (2nd July 2016) - Gebreegzainher, Kinfe Abraha
ABSTRACT: The livelihood of the population in general, and females in particular, is affected by different socio-economic, demographic, environmental, cultural and other factors. the three main demographic variables: fertility, mortality and migration, which are also functions of some other variables, determine the quality of women's lives. Some of the variables that are expected to determine the levels of fertility, mortality and migration may include literacy status, educational level, occupation, income, place of residence, marital status and other factors. Fertility is the most important variable in the population dynamics. A study was made in tigray, ethiopia, that included 2290 individuals. Of these, 1371 (60%) were females. the method of enumeration was used in order to collect the necessary information from the target population. the age structure, household composition, place of residence, educational level and other background variables were analysed. Results show that the literacy status and educational level were important variables that determined the age at first marriage, the use of family planning services, and antenatal and postnatal care. thus, it was concluded that female education is a key variable that enhances the participation of women in the development process by improving their status through the reduction of fertility.